2021
DOI: 10.1097/pcc.0000000000002704
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Communication Embedded Bedside ICU Rounds: A Hybrid Rounds Practice Adapted to the Coronavirus Pandemic

Abstract: Coronavirus disease 2019 containment strategies created challenges with patient-centered ICU rounds. We examined how hybrid rounds with virtual communication added to in-person rounds could facilitate social distancing while maintaining patient-centered care. DESIGN: Continuous quality improvement.SETTING: Quaternary care referral pediatric hospital.PATIENTS: Daytime rounds conducted on PICU patients. INTERVENTIONS:Following a needs assessment survey and pilot trials, multiple technological solutions were impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 25 publications
0
22
0
2
Order By: Relevance
“…It contains any issues that users find in using the systems. The studies on telehealth reported that screen freezing, audio delays [ 20 , 24 , 34 ], and alarm interference [ 29 ] impacted their interaction with patients during the virtual visits. As health care organizations rapidly implemented telehealth during the pandemic and workflows highly increased, there was a heavy load of data entry and a lack of time for it and documentation [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It contains any issues that users find in using the systems. The studies on telehealth reported that screen freezing, audio delays [ 20 , 24 , 34 ], and alarm interference [ 29 ] impacted their interaction with patients during the virtual visits. As health care organizations rapidly implemented telehealth during the pandemic and workflows highly increased, there was a heavy load of data entry and a lack of time for it and documentation [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The increased use of digital health has added another layer of interruption. Inconsistency in team communication [ 28 , 29 ]; difficulties in scheduling procedures [ 28 , 32 ], setting up different accounts, and obtaining various consents [ 30 ]; and constant updates [ 19 ] were among the issues the studies raised about workflows. The nurses were concerned about having the full responsibility for connectivity [ 23 ], which required extra time to communicate and coordinate visits [ 16 , 20 , 23 , 26 ], in turn limiting the number and efficiency of telehealth visits.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations